Design-driven innovation in design practice: The case of designing a ship-bridge vision - Kristiansen, Helge Tor; Gausdal, Anne Haugen (FormAkademisk, 2018)
The aim of this paper is to investigate Verganti’s framework for design-driven innovation (DDI) in the context of design practice and to discuss, elaborate and deepen the understanding of DDI, especially on aspects related to design. To meet this aim, an in-depth longitudinal case study of a DDI project for developing a radical new vision for an offshore ship bridge concept is performed. DDI is generally recognised as an in-depth research process, but we also approach it as a highly creative, generative process of design in which design artefacts serve as knowledge production and exploration. Therefore, Verganti’s divide between research and creativity and his critique of user centredness are challenged. The paper adds complementary understandings to Verganti’s framework, particularly regarding the role of design, and the Generative Design-Driven Innovation framework is developed.